The Holden story. - General Motors-Holden's Limited ([Fishermen's Bend, Vic.] : GMHA, 1990)
Poster showing 66 black and white photographs of Holden cars.
"12/90".
Available from GMHA, Fishermens Bend, Port Melbourne Vic 3207.
National Library of Australia's copy previously folded, shows vertical and horizontal fold marks.
Keywords: Holden automobiles; Holden automobiles -- Posters; Holden automobiles -- History; Holden automobiles -- History -- Posters